The Influence of Electronic Banking on Company Value with Profitability as a Mediating Variable - Pakiding, Daniel L.; Melyna, Melyna; Daromes, Fransiskus E. (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
This study aims to investigate the effect of electronic banking on profitability and its impact on firm value. Electronic banking under study is mobile banking. The basis used to explain the relationship between variables in this study comes from the RBV theory (resourced based view theory). The population used is banking companies listed on the Indonesia Stock Exchange (IDX) with a research period of 2017-2020. The number of samples is 40 companies each year, which are selected by purposive sampling method. This study uses documentary data, namely annual reports and financial reports. The results of this study indicate that electronic banking has a positive and significant effect on profitability. Electronic banking has a positive but not significant relationship to firm value. Sobel test (Sobel test) shows that profitability is able to mediate the relationship between electronic banking and firm value